Influência da cubagem rigorosa no ajuste de modelos de taper para eucalipto no sul do Tocantins - Glória Júnior, Murilo Azevedo (Universidade Federal do Tocantins, 2017)
The objective of this work was to evaluate taper models, together with two forms of absolute and relative rigor, for Corymbia citriodora in a commercial plantation located in the municipality of Dueré, southern region of the State of Tocantins. Data were collected from 35 sample trees, whose data were used in the adjustment of 5 taper models, Schöepfer, Demaerschalk, Ormerod, Hradetzky and Biging. In the evaluation of these, the statistical criteria were adopted: standard error of the estimate, adjusted coefficient of determination and mean deviation, and the complementary analysis of graphical distribution of the residues. It was concluded that the model of Hradetzky (1976) was the one that most fit to describe the profile of the trunk of the species Corymbia citriodora in the South region of Tocantins, and the model of Biging using the absolute cuba was the one that presented better prediction of the diameters , followed by Hradetzky, both being suitable to quantify multiproducts of the wood of Corymbia citriodora.